Towards a New Politics of Tradition? Decentralisation, Conflict, and Adat in Eastern Indonesia - Nils Bubandt (Antropologi Indonesia, 2004)
The intention of this article is to discuss the relationship between the processes of fiscal and political decentralization, the outbreak of communal violence, and what I call 'the new politics of tradition' in Indonesia. In 1999 under the President Jusuf Habibie, the Indonesian parliament (DPR) voted in favour of two laws, No. 22 and 25 of 1999, which promised to leave a significant share of state revenues in the hands of the regional governments. Strongly supported by the liberal ideologues of the IMF and the World Bank, the two laws were envisaged within Indonesia as a necessary step towards devolving the centralized power of New Order patrimonialism and as a way of curbing separatism and demands for autonomy by giving the regional governments the constitutional and financial wherewithal to maintain a considerable degree of self-determination. Decentralization was in other words touted as the anti-dote to communal violence and separatist tendencies-an anti-dote administered or at least prescribed by multi-national development agencies in most conflict-prone areas of the world. This paper wishes to probe this idea by looking at the conflict and post-conflict situation in North Maluku. The conflict illustrates how local elites began jockeying for political control in anticipation of decentralization. The process of decentralization is in other words not merely an anti-dote but in some cases an implicated part in the production of violence. One reason for this is simply that the decentralization of financial and political control after three decades of centralization entails a significant shift in the parameters of hegemony-a shift towards which local political entrepreneurs in the regions are bound to react. The new 'politics of tradition' currently emerging in Indonesia is the combined result of changes in global forms of governance, a strong political focus on ethnic and religious identity in the 'era reformasi' and a local willingness to employ these identities to garner support in the new political landscape of decentralization.